Comparison of Different MPPT Algorithms for PV System - Verma, Richa; Bhargav, B; Varma P, Srinivasa (International Journal of Engineering and Technology, 2018)
This paper helps us analyze three different MPPT techniques like Perturb and Observe, Incremental Conductance and Particle Swarm Optimization method. As the output characteristic depends on temperature and irradiance, therefore the maximum power point (MPPT) is not always constant. Hence it is necessary to ensure that the PV panel is operating at its maximum power point. There are many different MPPT techniques but, the confusion lies in selecting which MPPT technique is best as every algorithm has its own merit and demerit. In order to extract maximum power from PV arrangement, PSO algorithm is proposed. Algorithms are implemented using the DC-DC converter as well as SEPI converter. Results of simulations are presented in order to demonstrate the effectiveness of PSO algorithm, when compared to Perturb and Observe (P&O) and Incremental Conductance (INC). To simulate the proposed system MATLAB/SIMULINK power system tool box is used.Â